Pengaruh Lingkungan Kerja Terhadap Kinerja Karyawan PT. Jico Agung Palembang - Ria Purnama Sari; Roswaty Roswaty; Kurniawan Kurniawan (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
This study aims to investigate the influence of work environment on the performance of the employees of PT Jico Agung Palembang. Data obtained from 58 respondents consisting of leaders and all employees of PT Jico Agung Palembang. Data were collected through interviews, observations, and questionnaires and analysed using simple linear regression on SPSS. The results reveal that work environment has a positive and significant effect on performance. The relationship between work environment and performance is strong as indicated by the correlation coefficient of 73.5%. The determination test of 0.541 proves that the work environment affects performance by 54.1% and the remaining 45.9% is influenced by other variables outside of this study.